A review of residential heat decarbonisation in Ireland - Lynch, Muireann Á.; Tovar Reaños, Miguel; Farrell, Niall (ESRI, 2026)
Ireland’s Climate Action Plan targets rapid decarbonisation of residential heat, with 2030 targets for deep retrofits (500,000 homes to BER ≥B2), large-scale heat-pump deployment (400,000 in existing dwellings), and district heating (up to 2.7 TWh/yr). This article reviews progress to date and the empirical evidence on whether the current policy mix is likely to deliver the required emissions reductions. Using the latest administrative statistics, we show that delivery is materially off-track: by end-2024, deep retrofits reached 57,932 (11.5% of target) and heat-pump installations 14,194 (3.5% of target). Linear projections based on post-pandemic trends imply that even continued acceleration leaves substantial shortfalls by 2030, with district heating similarly unlikely to meet targets. We synthesise evidence on the barriers driving under-delivery—high household capital costs, disruption, administrative complexity, information constraints, and landlord–tenant split incentives—and highlight capacity trade-offs with housing supply via constrained construction labour and complementary electricity-network investment needs. We review the recent literature on retrofits to date, which shows that measured decarbonisation may be overstated because BER/EPC metrics can diverge substantially from actual energy use. Finally, we discuss supplementary policy pathways aimed at hard-to-reach households and system-wide efficiency: targeted fuel switching (including regulated renewable heat blends and sustainable liquid biofuels with robust traceability), more progressive targeting of supports toward low-income/high-impact homes, and enabling flexibility through smart controls and thermal energy storage. We conclude that meeting climate objectives will likely require both faster delivery of existing measures and additional, better-targeted interventions grounded in representative, data-driven evaluation.